2019
DOI: 10.32734/abdimastalenta.v3i2.4121
|View full text |Cite
|
Sign up to set email alerts
|

Using a “Snake and Ladder” Game in Teaching Speaking to Young Learners

Abstract: Speaking is the basic as well as the most important skill that needs to be acquired by English language learners. It is advisable that learning speaking English should begin as early as possible; however, to teach speaking skill to young learners is not an easy task since their age is the age of playing. Teaching speaking to young learners requires a teacher to find the technique best work with children, one of which is through games. One of the games that is corresponding to the age of young learners is a sna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…The use of games in dialogue learning is trusted to reduce students' anxiety pressure when online learning, while at the same time achieving learning objectives based on predetermined competencies and indicators. Saefullah, Romly & Abdullah (2019), cited in (Sofyan et al, 2019) explained that playing games in English dialogue invite students to speak in English and improve their English dialogue skills. Furthermore, Von Ann (2006) cited in Fakhrurrazy (2018) added that the use of games in learning is a fun activity through rules.…”
Section: Introductionmentioning
confidence: 99%
“…The use of games in dialogue learning is trusted to reduce students' anxiety pressure when online learning, while at the same time achieving learning objectives based on predetermined competencies and indicators. Saefullah, Romly & Abdullah (2019), cited in (Sofyan et al, 2019) explained that playing games in English dialogue invite students to speak in English and improve their English dialogue skills. Furthermore, Von Ann (2006) cited in Fakhrurrazy (2018) added that the use of games in learning is a fun activity through rules.…”
Section: Introductionmentioning
confidence: 99%
“…it will be a challenge if you can't speak English in this 4.0 industrial era because all items must have English writing such as on food wrappers or items you can see there are English writings such as throwing trash in its place, or ingredients for making food. Speaking is very important in learning a second language (Sofyan et al, 2019). We know the importance, speaking has been ignored in schools and universities for different reasons such as an emphasis on grammar and teachers who are sometimes vague or do not speak like teachers can sometimes be said to be disrespectful.…”
Section: Teaching Speakingmentioning
confidence: 99%
“…The knowledge in the memory (mind) can be retrieved at any time (Wulanyani, 2014). Several studies have shown that the game of snakes and ladders helps help children to understand better nouns and speaking skills in English (Musa et al, 2016;Sapungan, 2014;Sofyan et al, 2019). Snakes and ladders board games have the potential to promote students' desire to talk within peers group.…”
Section: Introductionmentioning
confidence: 99%